2022
DOI: 10.7759/cureus.27448
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of the Immunohistochemical Expression of Mismatch Repair Proteins (MSH2, MSH6, MLH1, and PMS2) in Prostate Adenocarcinoma

Abstract: Background and objectiveMismatch repair (MMR) proteins are an integral part of the cell cycle, and they play an important role in the genomic stability of the microsatellite complex. Microsatellite instability (MSI) is associated with Lynch and multi-tumor syndromes. Identifying patients with Lynch syndrome is essential for screening, early detection, and surveillance of other Lynch syndrome-associated tumors. The role of MMR deficiency is well known in colorectal and endometrial adenocarcinoma. However, the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 15 publications
(22 reference statements)
0
4
0
Order By: Relevance
“…MSH6 alterations have been reported in approximately 1% of PC cases [42,[59][60][61]. A loss of the immunohistochemical expression of MSH6 was found in 2.7-16.8% of PCs [48,49]. However, Alberto-Gonzalez et al, in their study, revealed MSH6 overexpression in 42.1% of the cases [62].…”
Section: Msh6mentioning
confidence: 86%
See 3 more Smart Citations
“…MSH6 alterations have been reported in approximately 1% of PC cases [42,[59][60][61]. A loss of the immunohistochemical expression of MSH6 was found in 2.7-16.8% of PCs [48,49]. However, Alberto-Gonzalez et al, in their study, revealed MSH6 overexpression in 42.1% of the cases [62].…”
Section: Msh6mentioning
confidence: 86%
“…Another study found PMS2 mutations in 0.4% of metastatic PC patients [59]. However, Sharma M. et al and Javeed S. et al, in their studies, revealed a loss of PMS2 expression in 12.3% and 12.2% of PCs, respectively [48,49]. Although MMR gene alterations are associated with a worse prognosis in PC patients, there are no exact data correlating the PC grade with PMS2 expression [63].…”
Section: Pms2mentioning
confidence: 96%
See 2 more Smart Citations